Business vocabulary builder : intermediate to upper-intermediate : the words & phrases you need to succeed. - Emmerson, Paul, ....- (Oxford : Macmillan, 2009)
A business vocabulary and practice course for students with an intermediate level of English or above. The course is specifically designed to help business English students enrich and expand their vocabulary, allowing them to express themselves more fluently and confidently in a professional context. The first part of the book focuses on business language input while the second part of the book is dedicated to prefessional communication skills and introduces language for telephoning, e-mailing, report writing and conferences. CONTENTS Business topics - The business world - Management - Production and operations - Sales and marketing - Company finance - Financial markets - Human resources Effective communication - You and your job - Telephoning - Emails - Presentations - Meetings - Business reports and proposals Speaking practice - Discussion topics Writing Practice - Writing tasks Listening practice - Interviews with business people : exercises Listening scripts - Listen and repeat exercises - Interviews with business people Answer key
Keywords: Zakelijke communicatie -- Engels